Effects of premature contact in maxillary alveolar bone in rats: relationship between experimental analyses and a micro scale FEA computational simulation study - Rossi, Ana Cláudia; Freire, Alexandre Rodrigues; Ferreira, Beatriz Carmona; Faverani, Leonardo Perez [UNESP]; Okamoto, Roberta [UNESP]; Prado, Felippe Bevilacqua (Springer Nature, 2021)
Objective: The aim of the investigation was to evaluate the maxillary alveolar bone morphology, bone architecture, and bone turnover in relation to the mechanical strain distribution in rats with dental premature contact. Materials and methods: Fifty 2-month-old male Wistar rats were used. The premature contact group (N=40) received a unilateral (right side) resin cementation on the occlusal surface of the upper first molar. The animals were distributed in 4 subgroups according to the periods of euthanasia: 7, 14, 21, and 28 days after cementation (N=10, for each period). For the control group (N=10), the teeth were kept without resin, featuring a normal occlusion. The pieces including the upper first molars, alveolar bone, and periodontal tissue were processed to histological and immunohistochemical evaluation of RANK-L and TRAP protein expression. A three-dimensional bone microarchitecture analysis was performed, where the heads of animals were scanned using microtomography and analyzed using CT-Analyser software (Bruker, Kontich, Belgium). In the computer simulation by finite element analysis, two micro-scaled three-dimensional finite element models of first molar and dentoalveolar tissues were constructed, in representation of control and premature contact groups, using Materialise MIMICS Academic Research v18 (Materialise, Leuven, Belgium). The analysis was set to simulate a maxillary molar biting during the power stroke phase. The total deformation, equivalent strain, and minimum principal strain distribution were calculated. Results: The expression of RANK-L and TRAP presented higher positive ratio in the 7-day period compared to the control group. The three-dimensional morphometry showed decrease of bone volume in the premature contact, with significant values between the control and the 7-day and 14-day groups (P = 0.007). In FEA, the premature contact model presented a uniform compressive strain distribution in the alveolar bone crest compared to a non-uniform compressive strain distribution in the control model. Conclusions: The results from FEA, 3D bone microarchitecture, and histological and immunohistochemical analyses showed that a model with dental traumatic occlusion resulted in changes of alveolar bone mechanobiology and, consequently, its morphology. Clinical relevance: These results could be applied in dental treatment planning bringing biological and mechanical feedback to provide an effective mechanism to obtain physiological bone loss responses. Furthermore, this association between experimental and computational analyses will be important to figure out the alveolar bone response to mechanical stimulation in different clinical conditions.
Keywords: Alveolar bone; Dental occlusion; Finite element analysis; Mechanobiology; Micro-CT; Premature contact; Rat